2023
DOI: 10.1073/pnas.2216507120
|View full text |Cite
|
Sign up to set email alerts
|

Autocorrelation analysis for cryo-EM with sparsity constraints: Improved sample complexity and projection-based algorithms

Abstract: The number of noisy images required for molecular reconstruction in single-particle cryoelectron microscopy (cryo-EM) is governed by the autocorrelations of the observed, randomly oriented, noisy projection images. In this work, we consider the effect of imposing sparsity priors on the molecule. We use techniques from signal processing, optimization, and applied algebraic geometry to obtain theoretical and computational contributions for this challenging nonlinear inverse problem with sparsity constraints. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Beyond its application to experiments, d iKam demonstrates that Kam's method is a feasible strategy for high-resolution reconstruction. Recent works have improved the viability of Kam's method by using sparsity (7) or neural network (36) priors; likewise, the search over the PDB using Kam's metric can be interpreted as simply running Kam's method under a very strong prior, where only a finite number of structures appear with nonzero probability. Our results suggest that, if one could formulate a tractable prior over the manifold of proteins, Kam's method could yield high-resolution reconstructions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Beyond its application to experiments, d iKam demonstrates that Kam's method is a feasible strategy for high-resolution reconstruction. Recent works have improved the viability of Kam's method by using sparsity (7) or neural network (36) priors; likewise, the search over the PDB using Kam's metric can be interpreted as simply running Kam's method under a very strong prior, where only a finite number of structures appear with nonzero probability. Our results suggest that, if one could formulate a tractable prior over the manifold of proteins, Kam's method could yield high-resolution reconstructions.…”
Section: Discussionmentioning
confidence: 99%
“…We detail the procedure for computing m 1 , m 2 and therefore d vKam in Appendix A.1. Under certain conditions, it has been demonstrated that the second moment of the image collection identifies the 3D structure uniquely (2)(3)(4)6,7) or up to a finite list of candidate structures. (8) In Section 4.2, we show that our metric is alike other similarity scores but remarkably does not rely on alignment.…”
Section: Definition Of Kam's Metricsmentioning
confidence: 99%
See 2 more Smart Citations